The character building concept for teenagers in the Qur’an; analytical study of Musa as story - Ramli, Angraini; Elatrash, Radwan Jamal Yousef (Borneo International Journal of Islamic Studies, 2020)
The moral decadency and its degradation specifically in teenagers considered as worldwide problem nowadays. Harassment, bullying cases and low ethic association in teenagers levels obviously appeared everywhere. Many other cases occurred as the result of ignorance from parents, community and all those who are responsible in their upbringing. Being captivated by gender stereotypes leads to inequality and inbalance which resulted low and poor character. Patriarchy culture caused female being subordinated male and male are not allowed to shed tears which leads to lack of emphathy they owned. The concept of character was beautifully mentioned in al-Qur’an through advices and stories from the Prophets. One of the most visible character raised is the story of Prophet Musa As. This paper analyses interactions between Musa As and the daughters of Prophet Syu’aibin the time of their teenage stage from surah al-Qasas. Itstated clearly about how and what are the balanced and a proper characters should be owned by all teenagers. It asserted that the perfections of Akhlāq and morals which is a symbolic of the beauty of akhlāq also the most important point in obtaining a high quality of life. This research The Character Building Concept for Teenagers in the Qur’an 113 Borneo International Journal of Islamic Studies,2(2), 2020 resulted that the building character of teenagers should combined all three system, such as Family, School and Community. Having a role model who posses a beautiful character will undeniably help. The Quran introduced a perfect role model from the Prophet stories denying all the gender stereotypes and patriarchy culturewhich usually leads to inequality in nurturing process.